THE INFLUENCE OF SMARTPHONE USE ON COMMUNICATION BEHAVIOR OF COMMUNICATIONS STUDENTS IN KALIMANTAN ISLAMIC UNIVERSITY MAB - Nopian Rahman; Hermansyah Hermansyah (Jurnal Scientia, 2022)
Smartphone is a new media in today's communication process. Not only used as a communication process, but smartphones are also able to help almost all the needs of human life. This study aims to determine what effect smartphone use has on affective, conative, and cognitive communication behavior in college students. Research conducted using descriptive quantitative research methods. This research was conducted at the Islamic University of Kalimantan MAB. The population is 311 students. The research sample was determined using the Slovin formula, a sample of 76 respondents was obtained. Data was collected using a questionnaire, the data collected was then presented in the form of a frequency table. The analysis technique used is simple linear regression analysis and t test. The results showed that there was an influence between the use of smartphones on student communication behavior. The tcount value is 3.211 and the ttable is 1.901, because tcount> ttable so Ha is accepted and Ho is rejected. In other words, reject the null hypothesis (Ho) and accept the alternative hypothesis (Ha) for testing the two variables. Meanwhile, the use of smartphones makes an effective contribution to student communication behavior by 45.8%. The cultivation theory initiated by George Gerbner has proven that mass media (smartphones) are able to influence audiences, one equates what is seen on television with something that is commonly done in the real world..